2017
DOI: 10.1111/jvs.12564
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and application of multiple potential natural vegetation models – a case study of Hungary

Abstract: QuestionsMultiple Potential Natural Vegetation (MPNV) is a framework for the probabilistic and multilayer representation of potential vegetation in an area. How can an MPNV model be implemented and synthesized for the full range of vegetation types across a large spatial domain such as a country? What additional ecological and practical information can be gained compared to traditional Potential Natural Vegetation (PNV) estimates? Location Hungary MethodsMPNV was estimated by modelling the occurrence probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 57 publications
1
28
0
4
Order By: Relevance
“…In the course of the modeling, Gradient boosting models (Elith et al ) were used to relate the abiotic conditions to the observed presence of natural vegetation types. The statistical relationships identified were used to estimate presence probabilities of vegetation types as defined in the national habitat classification system (Bölöni et al ) for the whole country including areas currently devoid of natural vegetation (Somodi et al ). The same 35 ha resolution (of adjacent hexagons) was used for the predictions as the input vegetation data were available in this scale (MÉTA database; Molnár et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the course of the modeling, Gradient boosting models (Elith et al ) were used to relate the abiotic conditions to the observed presence of natural vegetation types. The statistical relationships identified were used to estimate presence probabilities of vegetation types as defined in the national habitat classification system (Bölöni et al ) for the whole country including areas currently devoid of natural vegetation (Somodi et al ). The same 35 ha resolution (of adjacent hexagons) was used for the predictions as the input vegetation data were available in this scale (MÉTA database; Molnár et al ).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of the modeling, Gradient boosting models (Elith et al 2008) were used to relate the abiotic conditions to the observed presence of natural vegetation types. The statistical relationships identified were used to estimate presence probabilities of vegetation types as defined in the national habitat classification system (Bölöni et al 2011) for the whole country including areas currently devoid of natural vegetation (Somodi et al 2017 also on the data characteristics per vegetation type, which is an undesirable property. Habitats with few occurrences due to specific environmental requirements but not due to human intervention and widespread zonal types achieve high probabilities in absolute, but those with few occurrences due to conversion by humans have lower probabilities even where they are relatively probable compared to their own distribution.…”
Section: Priorities Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these simplifications, the model accuracy is good. The validation of ecological models against expert‐based PNV maps in areas where the actual vegetation cannot be used because of strong anthropogenic modification is common practice (Hickler et al, ; Somodi et al, ). We chose the fuzzy approach to assess the agreement because it allowed the consideration of similarities between the vegetation communities along the successional gradient from “initial phase” to the “terminal stage” and the consideration of spatial proximity between cells.…”
Section: Discussionmentioning
confidence: 99%
“…Potential natural vegetation (PNV) is that which grows in a natural environment without human intervention (Tüxen, 1956). PNV could serve as a restoration reference (Loidi et al, 2010;Somodi et al, 2017;Zerbe, 1998), but there have been objections to its implementation.…”
Section: Introductionmentioning
confidence: 99%